Effects of cardiac function alterations on the risk of postoperative thrombotic complications in patients receiving endovascular aortic repair - Sun, Xiaoning; Li, Siting; He, Yuan; Liu, Yuxi; Ma, Tianxiang; Zeng, Rong; Liu, Zhili; Chen, Yu; Zheng, Yuehong; Liu, Xiao (Frontiers in Physiology, 2023)
Chronic heart disease (CHD) is a common comorbidity of patients receiving endovascular aneurysm repair (EVAR) for abdominal aortic aneurysms (AAA). The ventricular systolic function determines the hemodynamic environments in aorta, and thus regulating the formation of postoperative thrombus. However, the explicit relationship between ventricular systolic function and EVAR complication of thrombotic events is unknown. Here, we proposed a three-dimensional numerical model coupled with the lumped-elements heart model, which is capable of simulating thrombus formation in diverse systolic functions. The computational results demonstrate that thrombus tended to form on the interior side of the aorta arch and iliac branches, which is consistent with the four patients' post-operative imaging follow-up. In addition, we found that the thrombus formation has negative correlations with the maximum ventricular contractile force (r=-0.2814±0.1012) and positive correlations with the minimum ventricular contractile force (r=0.238±0.074), whereas the effect of heart rate (r=-0.0148±0.1211) on thrombus formation is not significant. In conclusion, changes in ventricular systolic function may alter the risk of thrombotic events after EVAR repair, which could provide insight into the selection of adjuvant therapy strategies for AAA patients with CHD.